Telangiectatic osteosarcoma affecting the mandible - Naik, LR Kumaraswamy (Medknow Publications & Media Pvt Ltd, 2014)
Osteosarcomas are relatively rare in jaws and maxillomandibular lesions in children are distinctly uncommon. Telengiactic osteosarcomas in jaws are still a very rare variant and till now just 3 cases are reported in English literature. Herein, we report the first case of telangiectatic osteosarcoma occurring in mandible in pediatric patient. Patient was treated by hemimandibulectomy and is free of disease since seven years with regular follow-up.